Implementasi Layanan Bimbingan Konseling Islami dalam Meningkatkan Motivasi Belajar Siswa Kelas XI di SMA Al-Ulum Medan - Herwina Azhabi; Saiful Akhyar Lubis; Edi Saputra (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2019)
This research is backed by the interest of researchers to research the discipline and motivation of learning students at Al-Ulum High School Medan. This research aims to determine how the efforts of the teachers of BK in improving the motivation to learn the students of XI class in Al-Ulum High School Medan. See what obstacles in improving the motivation of grade XI students in SMA Al-Ulum Medan. The method used in this study is qualitative in a narrative approach, which is a research procedure that generates a detailed data of the written or oral words of the observed behavior.The results of the implementation of Islamic counseling services in improving the motivation to learn students of XI class in Al-Ulum SMA Medan namely: first, the efforts of teachers of BK in increasing the motivation to learn student XI class by applying the principles In the guidance of Islamic counseling, so that the results achieved good learning. This can be seen from the student's success to complete the process of learning at Al-Ulum school in Medan. Secondly, the obstacles in increasing the motivation to learn the students of XI grade in SMA Al-Ulum are: the background of counseling teachers who are not from education counselling tutoring and need to plus one more teacher BK, see there is only one BK teacher in high school Al-Ulum Medan. Parents who are not exposed to the issue of students who need counseling guidance.